Critical Evaluation of Native Electrospray Ionization Mass Spectrometry for Fragment‐Based Screening. (25th July 2017) - Göth, Melanie; Badock, Volker; Weiske, Jörg; Pagel, Kevin; Kuropka, Benno
Abstract: Fragment‐based screening presents a promising alternative to high‐throughput screening and has gained great attention in recent years. So far, only a few studies have discussed mass spectrometry as a screening technology for fragments. Herein, we report the application of native electrospray ionization mass spectrometry (MS) for screening defined sets of fragments against four different target proteins. Fragments were selected from a primary screening conducted with a thermal shift assay (TSA) and represented different binding categories. Our data indicated that, beside specific complex formation, many fragments show extensive multiple binding and also charge‐state shifts. Both of these factors complicate automated data analysis and decrease the attractiveness of native MS as a primary screening tool for fragments. A comparison of the hits identified by native MS and TSA showed good agreement for two of the proteins. Furthermore, we discuss general challenges, including the determination of an optimal fragment concentration and the question of how to rank fragment hits according to their affinity. In conclusion, we consider native MS to be a highly valuable tool for the validation and deeper investigation of promising fragment hits rather than a method for primary screening. Abstract : Does mass matter? Defined sets of fragments were screened against four target proteins by using native mass spectrometry (MS). Beside specific complex formation, many fragments show multiple binding and charge‐state shifts. These factors complicate automated data analysis and diminish the attractiveness of native MS as a primary fragment screening tool. However, a comparison of the hits identified by native MS and thermal shift assays shows good agreement for two of the target proteins.